A Tahlili Study Was Conducted on The Hadith Regarding The Guardianship of A Widow in Marriage - Haris, Gaffar (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2023)
In marriage, one of the individuals entitled to represent and administer the rights of a person is the Wali. In the case of a widow's marriage, the role of the guardian is crucial to ensure that the widow's rights are recognized and fulfilled. This study uses descriptive qualitative methods with a sociological approach to examine the guardianship rights of widows. The field data is compared with the findings of hadiths that discuss the widow's guardianship using the tahlily method to analyze the hadith maānil. The research concludes that the traditions that explain the guardianship of a widow allow widows to choose their partners, but do not deny their guardianship rights. The relevant traditions clarify that widows have the authority to choose their partners even if their guardians do not approve of it, but the Prophet advised widows to respect the existence of their guardians even though they have been granted full rights